Pengaruh Aplikasi Gliserin pada Kekerasan Resin Komposit Nanofiller dengan Perendaman Cuka Apel - Raditya Nugroho; Putri Nila Kharisma; Roedy Budirahardjo (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Composite resin is a type of filling material that is often used because it has good bonds with dentine and enamel and has a high aesthetic value. Nanofiller composite resin has high hardness, good polishing, color accuracy, and good translucency. The hardness of composite resins can change caused by low pH beverage. Purpose: To determine the differences in effect of glycerin application on hardness of nanofiller composite resins with immersion of apple cider vinegar. The type of research used was experimental laboratories with a pretest and post test group design. Samples were 24 immersion in apple vinegar for 60 and 120 minutes. Measurement of hardness using the Vicker Hardness Tester to determine the hardness value. Data analysis was performed using One Way Anova and Post-Hoc LSD tests.There is a significant difference in the value of composite resin hardness in the entire study group. The highest hardness value was found in the group with the application of glycerin and without immersion, while the lowest value was found in the group without the application of glycerin and immersion in 120 minutes.